Marketing of environmentally friendly hotels in China through religious segmentation: a theory of planned behaviour approach - Lei, Wang; Wong, P. P. W. * (Emerald, 2020)
Purpose – The purpose of this study is to examine the relationship between religiosity, green purchase attitude (GPA), subjective norm (SN), perceived behavioural control (PBC) and green purchase intention (GPI) towards the selection of environmentally friendly hotel. The current study argues that consumers’ incentive variable, namely, religiosity, can influence consumers’ environmentally friendly hotel selection. Design/methodology/approach – This study had successfully gathered 404 completed questionnaire sets through online surveys. All survey data were subjected to descriptive analysis and analysis of variance using SPSS. Besides that, confirmatory factor analysis and structural equation modelling were performed for the testing of hypotheses. Findings – The results suggest that religiosity significantly and positively influences GPA, SN, PBC and GPI. Furthermore, GPA and PBC positively and significantly influence GPI. The SN also displays significant positive influence on GPA, while GPA plays a full mediation role between SN and GPI. In addition, statistically significant differences in religiosity, SN and PBC were obtained between religious affiliations of consumers towards environmentally friendly hotel selection. Originality/value – This study extended the existing knowledge based on the selection of environmentally friendly hotels among religious consumers in the tourism literature. Besides that, these empirical findings would greatly benefit hotel managers and other key stakeholders in the tourism industry.